Prognostic role of the pathological status following neoadjuvant chemoradiotherapy and surgery in esophageal squamous cell carcinoma - Xiaofeng Duan; Jie Yue; Shangren Wang; Fangdong Zhao; Wencheng Zhang; Shuo Qie; Hongjing Jiang (BMC Cancer)
Abstract Background In this study, we retrospectively examined the prognostic significance of the pathological status of esophageal squamous cell carcinoma (ESCC) patients following neoadjuvant chemoradiotherapy (NCRT) and surgery. Methods Data of patients with cT2-4aN0-3 stage ESCC who underwent NCRT and esophagectomy during 2014–2022 were reviewed retrospectively. Survival differences were compared according to revised TN (rTN) stage (ypT0N0, ypT + N0, ypT0N+, and ypT + N+) using univariate and Cox regression analyses. Results Of the 136 patients (59.1 ± 7.2 y) included in this study, 123 (90.4%) were males. There were 39 (28.7%) patients with ypT0N0 disease, 49 (36.0%) ypT + N0, 11 (8.1%) ypT0N+, and 37 (27.2%) ypT + N+. Additionally, 126 patients had a median follow-up period of 30 (1–90) months. The 5-year overall survival was 81.6% in ypT0N0 group, 53.1% for ypT + N0, 50.0% for ypT0N+, and 18.6% for ypT + N+ (p < 0.001) and 5-year disease-free survival was 70.1% for ypT0N0, 39.7% for ypT + N0, 33.3% for ypT0N+, and 18.4% for ypT + N+ (p < 0.001). The ypT + N0 and ypT0N + groups showed no significant differences in survival (p > 0.05). In Cox regression analysis, ypT stage and rTN stage showed an independent association with OS (p = 0.026 and 0.001, respectively). During the follow-up period, 69 (54.8%) patients developed recurrence, with ypT0N0 patients experiencing fewer local and distant recurrences compared to other groups (p < 0.001). Conclusion In ESCC patients, the ypT0N0 status after NCRT predicts prolonged survival, but this reduces significantly when nodal metastases or residual primary lesions are present.